Juventude e mídia tribunal: produção de sentido no programa Correio Verdade. - Mendes, Sheylla Maria (2009)
The present academic study proposes to analyse the kind of approach used by the broadcasted media (television) in situations which poor young people get involved in violent affairs. The chosen empirical source was the TV news known as Correio Verdade broadcasted by Sistema Correio de Telecomunicações, a TV station from Rede Record de Telecomunicações in Paraiba State. The selected hypothesis for this study is that, focusing on youngsters, the TV program judges and condemns those people as if assuming the duty of a kind of legal media. During the TV program we found the parts of a trial such as defendants (young people involved in violence), prosecutors, accusing witnesses and judges. The methodology used for such study dealt with the analysis of verbal, visual and sound language in order to learn the different strategies used by the TV program that aims to make sense, convince the audience and judge the focused youngsters. We analysed the opening headpiece of that TV program as well as the part of that program called Os Inocentes (The innocents) besides ten reportages that focused on situations of violence involving young people. The obtained data demonstrated how often those poor youngsters are shown on that mentioned program as well as the way they are seen in comparison to wealthy youngsters. On that TV program, poor young people are judged and considered guilty in a trial with no lawyers and opportunities to defence. The pictures, discourse and sound strategies shown on the TV program build the image of a hopeless criminal, without legal rights, for whom there is no possible solution. The legal media determines the verdict, contributing to the social view over those poor young people.